Analysis of Single Frame Super Resolution Methods (International Journal of Engineering and Computer Science, 2014)
The quality of Image is measured in terms of Resolution. The image clarity can be measured by Resolution. Better resolution can be generated by use of Good Sensors, but it can be very expensive .Instead of that we can use image processing methods to obtain High resolution image from low resolution image. It can be very effective and better solution. This Kind of Image Enhancement is called Super Resolution Image Reconstruction.This paper focuses on the definition, implementation and analysis on well-known techniques of super resolution. Image super-resolution, a process to enhance image resolution, has important applications in satellite imaging, high definition television, medical imaging, etc. Many existing approaches use multiple low resolution images to recover one high-resolution image. As a result of the analysis, the critical examination of the techniques and their performance evaluation are achieved.Super-resolution image restoration has been one of the most important research areas in recent years which goals to obtain a high resolution (HR) image from low resolutions (LR) blurred, noisy, under sampled and displaced image.